pH Dependence of Noble Metals Dissolution: Ruthenium - Mária Minichová; Tatiana Priamushko; Matej Zlatar; Karl J. J. Mayrhofer; Serhiy Cherevko (ChemElectroChem)
Abstract Ruthenium (Ru) or Ru‐based catalysts are widely used in various electrochemical applications such as biosensors, ammonia synthesis, CO2 reduction, electrolyzers, or fuel cells, operating at different conditions. While the activity of these catalysts is widely studied, works addressing stability are less common, especially in neutral or alkaline environments. Therefore, we evaluate a real‐time potential‐dependent dissolution of polycrystalline Ru via scanning flow cell coupled to inductively coupled plasma mass spectrometry in acidic, alkaline, and phosphate buffer electrolytes using relevant potential ranges. On top of the fundamental understanding of Ru's dissolution, a particular focus lies on oxygen evolution reaction (OER) due to its importance in various electrochemical applications. We show that the dissolution behavior of Ru during dynamic operation is well in line with the thermodynamic predictions (except dissolution due to Ru2+ formation) and unique compared to other noble metals (Pt, Au, Ir). While the dissolution of polycrystalline Ru is the highest in alkaline pH at the onset of OER (1.4 VRHE), no stability issues are visible at potentials up to 0.85 VRHE at all pHs. This work establishes a stability baseline for researchers implementing Ru‐based catalysts.